The Correlation Between Physical Activity and Sleep Quality in Elderly Outpatients with Hypertension at Sokaraja I Public Health Care Center, Banyumas Regency - Septiana Wahyuningsih; Nur Isnaini (UM Purwokerto Press, 2024)
Background: Physical activity is one effort that can control blood pressure in people with hypertension. Physical activity that is carried out excessively will result in a person experiencing fatigue easily so that it will have an impact on the quality of his sleep. Objective: This study was to determine the relationship between physical activity and sleep quality in elderly outpatients with hypertension at the Sokaraja 1 Public Health Center, Banyumas Regency. Method: This type of search used correlational analysis with a cross-sectional design approach. The time of the study was from February to March 2023. The population in this study were elderly outpatients with hypertension at the Sokaraja 1 Health Center, Banyumas Regency. The sampling technique used a non-probability sampling technique with purposive sampling, namely as many as 59 respondents. Results: The results showed that most respondents did heavy physical activity as much as 23 (39.0%), and respondents who had good sleep quality as many as 39 (66.1%). of statistical tests using the Chi-Square test obtained the results of calculating p-value = 0.00 <? = 0.05 so that Ho was rejected and Ha was accepted. Based on the results of this research, it can be concluded that there is a relationship between physical activity and sleep quality in the elderly in Sokaraja I public health care center, Banyumas Regency. Conclusion: It can be concluded that there is a relationship between physical activity and sleep quality in elderly outpatients with hypertension at the Sokaraja 1 Public Health Center, Banyumas Regency. The heavier the activity, the better the quality of sleep so that blood pressure can be controlled and can reduce the risk of complications.